Youth sexual aggression and victimization (Y-SAV) in Cyprus and Greece - Kouta, Christiana; Hadjigeorgiou, Eleni; Papadakaki, Maria; Chliaoutakis, Ioannis (My University, 2016)
© 2016, Hellenic Nurses Association. All rights reserved. Introduction: Youth sexual aggression and victimization is a universal problem as has physical and psychosocial effects in young people. Greece and Cyprus are two countries in the same geographical region and it will be very useful to explore research findings concerning youth sexual aggression and victimization in both countries. Aim: To describe the phenomenon of youth sexual aggression and victimization in Greece and Cyprus and to compare the prevalence rates between the two countries. Material and Method: Descriptive study, which was part of the European Y-SAV research project. A convenient sample was used, consisted of 584 young men and women from Greece (n=292) and Cyprus (n=291). Recruitment of the participants was done through youth networks and higher education institutes in the two countries and data selection was performed using the online questionnaire SAV-S, of Krahe and Berger (2013), that examines the different ways of victimization: (1) use/threat of physical violence (2) taking advantage of the weakness of a person to resist to an unwanted sexual contact and (3) verbal abuse and (4) other. Statistical analysis was performed using SPSS ver. 22.0 (p≤0.05). Results: In Cyprus, 11.8% of men reported at least one form of sexual aggression perpetration as compared to 3.3% of women. In Greece, 48.7% of men reported at least one form of sexual aggression per penetration and 14.8% of women and this gender difference was statistically significant. Data showed that youth sexual aggression and victimization is higher in Greece than in Cyprus. Conclusions: Youth sexual aggression and victimization are existing problems in both countries with serious psychosocial consequences. Data showed that the preventative and treatment measures are limited. These results may help in the design of effective preventative strategies and interventions.
Keywords: Aggression; Risky sexual behaviors; Sexual; Victimization; Youth